Chitosan-Based Formulations Intended as Protective Spray for Mask Surfaces in Prevention of Coronavirus Dissemination - Ayala Peña, Victoria Belen (2022)
The extraordinary occurrence of COVID-19 by the fast expansion of viral infections has propelledparticular interest in developing novel antiviral and virucidal agents to guarantee personalsecurity. The main objective of this work is to propose novel formulations able to optimize theuse of personal protection elements. In recent years, chitosan (CH) has attracted attention forbeing an interesting multifunctional, biodegradable, non-antigenic, non-toxic, andbiocompatible natural polymer with antimicrobial properties. In this work, formulations basedon a CH matrix containing silver, and Copper based nanoparticles have been developed. Thenovelty of this proposal is that almost liquid formulations have been reached, possessing verifiedproperties to inhibit evolved virus such as herpes simplex type 1 (HSV-1) and bovinebetacoronavirus 1 (BCoV-1), the latter belonging to the same family of the well-known the wellknownSARS-COV-19. Besides antibacterial bioactivity; as well as the ability of these formulationsto be easily sprayed on various surfaces, including conventional face masks, have been verifiedand discussed. The results presented in this contribution provide strong evidence on CH films asan ideal biosafe surface-protective for several daily used materials including the conventionalface masks.